PROSES PENUAAN OTAKBAGAIMANA KITA BISA MENCEGAHNYA - Fenny L. Yudiarto*, Hasan Sjahrir** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTIONAGING IS NOT SAME AS A DISEASE BUT AGING CAN STIMULATE SOME DISEASES SUCH AS NEURODEGENERATION CANCER AND ATHEROSCLEROSIS WE CAN NOT PREVENT THE AGING AGING IS A GIVEN WHAT WE CAN DO IS SLOWING THE RATE OF AGING PROCESS TO AVOID THE FRAILTY OR THE IMPACT OF AGING TO ACHIEVE THE LONGEVITY MANY THEORIES HAVE BEEN PUBLISHED TO EXPLAIN THE AGING PROCESS SHORTENING THE TELOMERE AND EXCESSIVE FREE RADICAL PLAY AN IMPORTANT ROLE TO STIMULATE DNA DAMAGE AND GENOMIC INSTABILITY ALSO INCREASE ACTIVITY OF ONCOGENE CALORIE RESTRICTION EXERCISE RESVERATROL STATIN ENOUGH SLEEP INTAKE PUFA VITAMINS B6 B12 AND FOLIC ACID PDE5 INHIBITOR HAVE BEEN PROVED TO DELAY THE AGING PROCESS